2005
DOI: 10.1039/b410014j
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hydrogenation reactions in a tube reactor packed with Pd/C

Abstract: Continuous flow of the substrate solution and hydrogen gas through a tube reactor packed with Pd/C catalyst brings about a highly reactive and efficient hydrogenation system, which converts 4-cyanobenzaldehyde to the benzyl alcohol derivatives at 25 degrees C, and at 90 degrees C, the cyano group becomes reduced to give the corresponding amine and toluene derivatives within 2 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…At temperatures up to 200 • C and ambient pressure Surangalikar et al and Besser et al [33,34] conducted the same reaction in the gas phase over sputtered Pt catalyst, where the reaction was limited by the intrinsic reaction rate. Continuous high-pressure hydrogenation reactions in small tube reactors with inner diameters of 1 and 4 mm, respectively have been presented by Desai and co-worker and Yoswathananont et al [35,36].…”
Section: Hydrogenations In Microreactorsmentioning
confidence: 97%
“…At temperatures up to 200 • C and ambient pressure Surangalikar et al and Besser et al [33,34] conducted the same reaction in the gas phase over sputtered Pt catalyst, where the reaction was limited by the intrinsic reaction rate. Continuous high-pressure hydrogenation reactions in small tube reactors with inner diameters of 1 and 4 mm, respectively have been presented by Desai and co-worker and Yoswathananont et al [35,36].…”
Section: Hydrogenations In Microreactorsmentioning
confidence: 97%
“…The authors also noted that the flow system performed more efficient hydrogenations compared with the batch system. [44] Asymmetric transfer hydrogenation of acetophenone 10 yielding (S)-1-phenylethanol (12) was also successfully carried out in the flow-through mode (Scheme 4). The column reactor was filled with NH-benzyl-(1R,2S)-norephedrine 11, covalently immobilized on silica gel and finally activated ruthenium.…”
Section: Continuous Catalysis With Packed Columnsmentioning
confidence: 99%
“…A similar approach was disclosed by Sato and co-workers. [44] They demonstrated the efficient continuous hydrogenation of 4-cyanobenzaldehyde to the corresponding 4-cyanobenzyl alcohol at RT using a similar gas-liquid-solid microflow system. At elevat-ed temperature (95 8C) the cyano group is also reduced.…”
Section: Continuous Catalysis With Packed Columnsmentioning
confidence: 99%
“…We recently have shown that stable dispersions of the Au-poly- (3,4) catalyze this reaction with an apparent rate constant of 43.9 9 10 -3 s -1 . The premise of the present investigation is that palladium (Pd), with its catalytic ability to effect hydrogenation reactions [17][18][19] can be a suitable candidate for carrying out reduction of nitrophenol and hence be of significance to the synthesis of nanocomposites. Interestingly, we found that the salts of Pd can oxidize the thiophene moiety to produce its conducting polymer while also undergoing reduction to Pd nanoparticles, in this process.…”
Section: Introductionmentioning
confidence: 99%